A SYNTACTIC PORTRAYAL OF PRIMARY AUXILIARY VERBS IN O.HENRY'S THE GIFT OF MAGI - Wa’özisökhi Nazara; Yusmalinda Yusmalinda; Wisewarna Nazara (Sekolah Tinggi Bahasa Asing Prayoga Padang, 2026)
This is a brief analysis of the primary auxiliary verbs in the classic short story The Gift of the Magi authored by O. Henry. It typically portrays how the primary auxiliary be, do and have are constructed and distributed within the sentences of O. Henry’s The Gift of the Magi. This analysis employs qualitative syntactic approach. The data analyzed for the sentences containing the primary auxiliary verbs be, do and/or have in The Gift of the Magi. The data gathered using non-participatory observation were analyzed using distributional method. The result of the analysis confirms that the primary auxiliary verbs bear grammatical meaning, signal aspect, or form voice. They Among the three primary auxiliaries identified with sentences of the short story, the primary auxiliary be appears most dominant, mostly distributed directly behind the subject.